Understanding the Factors that Influence Students' Behavior: Key towards an Effective Teaching - Januard Deñola Dagdag; Milky Mae D. Bandera (Pedagogi: Jurnal Ilmu Pendidikan, 2021)
Teachers' duty is to teach. But in honesty, teachers do many things. Aside from relaying the information that their students need to learn, they are also responsible for handling each student with different characteristics and behaviors. Thus, it is a problem if teachers do not know how to facilitate them as well as if they do not have enough understanding of educational psychology. Knowing and understanding students' cause of different behaviors is one way for teachers to facilitate their students appropriately and can teach effectively. This article then discusses salient factors that lead student to behave in such ways. It also gives emphasis on how a teacher will become effective in teaching if she first learn the root of students' behavior.